2017
DOI: 10.15517/aie.v17i1.27204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scaffolded intensive reading on students’ reading comprehension performance

Abstract: This research sought to explore the connection between a small-group intensive reading comprehension project and students’ performance in two sample English national exit exams (ENEEs) developed by the Ministry of Public Education, Costa Rica. The data were gathered from an intervention plan that combined the theoretical principles of schema theory, scaffolded reading comprehension, and intensive reading. The study adopts an action-research approach and uses a mixed design that combines quantitative and qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Moreover, (Sari & Huzairin, 2012) in their study how to improve students' vocabulary through intensive reading, the final analysis of the results showed that there was a significant improvement in students' vocabulary achievement after they were taught by using intensive reading, which emphasize that intensive reading can improve students' vocabulary achievement.In addition (Morales, 2017) in his study proves that intensive reading has a positive effect on scaffold reading. Figure 1 Shows Vocabulary Improvement…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, (Sari & Huzairin, 2012) in their study how to improve students' vocabulary through intensive reading, the final analysis of the results showed that there was a significant improvement in students' vocabulary achievement after they were taught by using intensive reading, which emphasize that intensive reading can improve students' vocabulary achievement.In addition (Morales, 2017) in his study proves that intensive reading has a positive effect on scaffold reading. Figure 1 Shows Vocabulary Improvement…”
Section: Discussionmentioning
confidence: 84%
“…According to previous studies [34]- [36], sample sizes comparable to those described in this study have been evaluated in a similar manner. Moreover, the insight reinforced by the process of sampling in the current study, noted in Morales [15] action research, was that a contextualized study like this should not aim to generalize any findings as applicable to a large sample though the researchers should closely examine any recurring patterns or themes that may emerge.…”
Section: Sampling Criteriamentioning
confidence: 99%
“…Soft refers to scaffolding by asking questions or giving constructive feedback, and hard scaffolding refers to helping with higher level thinking by giving hints or clues in solving difficult tasks. A review of some other action research articles, on English writing [11], [24]- [26], speaking [7], [9], [27], [28] or reading [8], [12], [13], [15] informed about new practices. However, most were conducted at the school level or were quasi experimental in design and implementation (pre-test post-test control group).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, intensive reading equips students with basic reading strategies to permit them to attain fluency and competence in the fields of vocabulary recognition and to increase their critical thinking skills (Jeanne Wanzek, 2014). Therefore, the students must precisely understand the text details, facts, concepts, opinions, and experiences (Sevilla, 2017). A message occurs in discourse; alongside, the purpose of intensive reading is to promote the reading ability in comprehending the whole contents of text (Miftah, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%